Using the ROSS optical streak camera as a tool to understand laboratory experiments of laser-driven magnetized shock waves. (21st May 2018) - Liao, Andy; Hartigan, Patrick; Fiksel, Gennady; Blue, Brent; Graham, Peter; Foster, John; Kuranz, Carolyn
Abstract : Supersonic flows with high Mach number are ubiquitous in astrophysics. High-powered lasers also have the ability to drive high Mach number, radiating shock waves in laboratory plasmas, and recent experiments along these lines have made it possible to recreate analogs of high Mach-number astrophysical flows under controlled conditions. Streak cameras such as the Rochester optical streak system (ROSS) are particularly helpful in diagnosing such experiments, because they acquire spatially resolved measurements of the radiating gas continuously over a large time interval, making it easy to observe how any shock waves and ablation fronts present in the system evolve with time. This paper summarizes new ROSS observations of a laboratory analog of the collision of a stellar wind with an ablating planetary atmosphere embedded within a magnetosphere. We find good agreement between the observed ROSS data and numerical models obtained with the FLASH code, but only when the effects of optical depth are properly taken into account.